Consumer redress mechanisms in Malaysia: prospects and challenges - Amin, Naemah (International Islamic University Malaysia, 2007)
An efficient, inexpensive and informal redress machinery is indeed essential for attaining consumer protection. In this respect the ordinary court system in Malaysia is generally perceived to be unable to satisfy consumers’ needs. Thus the establishment of the Tribunal for Consumer Claims in 1999 and the Tribunal for Homebuyer Claims in 2002 may be considered as two major landmarks in the development of consumer protection law in Malaysia. It is the aim of this paper to examine the current status of these two Tribunals, which shares many common features save for the jurisdiction. Although records show that the Tribunals have received tremendous response from consumers in Malaysia, there are yet many improvements to be made. In addition this paper examines the challenges faced by the Tribunals in the course of offering informal, faster and cheaper procedure to consumers. Some of these major challenges are enforcement of theTribunals judgement, accessibility, publicity and judicial review.